Looking for truths in the stories we tell in queer communication studies. Issue 2 (3rd April 2021) - Spencer, Leland G.
ABSTRACT: This article offers two suggestions for the future of queer communication studies: First, we should continue to use language carefully and thoughtfully, especially about gender, sex, gender identity, and sexual orientation. Second, queer communication scholarship should be intentionally and meaningfully intersectional, eschewing superficiality and tokenism related to race, ethnicity, and nationality.